Fewer babies and more robots: Economic growth in a new era of demographic and technological changes - Juan F. Jimeno (SERIEs - Journal of the Spanish Economic Association, 2019)
This paper surveys recent research on the macroeconomic implications of demographic and technological changes. Lower fertility and increasing longevity have implications on the age population structure and, therefore, on the balance between savings and investment. Jointly with meagre productivity growth, this implies a low natural rate of interest that conditions the effectiveness of monetary and fiscal policies, especially in a world of high debt. New technological changes (robots, artificial intelligence, automation) may increase productivity growth but at the risk of having disruptive effects on employment and wages. The survey highlights the main mechanism by which demographic and technological changes, considered both individually and in conjunction, affect per capita growth and other macroeconomic variables.
Keywords: J11; O33; O41; 330; Population ageing; Technological progress; Innovation; Automation; Economic growth